Addressing Health Inequities in Maternal and Child Healthcare In Low-Income Communities - Emma Thompson; James Moore (International Journal of Health and Medicine, 2024)
This study investigates health disparities in maternal and child healthcare within low-income communities. By analyzing healthcare access, quality, and outcomes, the research highlights factors contributing to health inequities, such as socioeconomic status, education level, and healthcare infrastructure. The findings underscore the need for targeted policy interventions and community health programs to address these disparities and improve maternal and child health outcomes.